Uso da pele de tilápia descelularizada como xenoenxerto no tratamento de defeitos de córnea experimentais em ratos - Pompeu, Raquel Pinheiro Nogueira (2023)
Corneal ulcer is an ophthalmic emergency, defined by the loss of integrity of its epithelium and underlying stromal infiltration by leukocytes, associated with inflammatory signs. Considering the proven efficacy of using Nile tilapia skin in second-degree burns in humans, the question arises whether this biological matrix would be beneficial in other types of wounds. Thus, the aim of this study was to evaluate the utility of the decellularized Nile tilapia skin matrix as a xenograft in the treatment of experimental corneal ulcers in rats, compared with grafting with bovine amniotic membrane and with non-intervention, i.e., spontaneous healing of the ulcerated area. For this purpose, an assay was designed involving the induction of corneal ulceration through trephination in Wistar rats (Rattus norvegicus), which were divided into three experimental groups: Control, consisting of animals in which healing of the ulcerated area occurred spontaneously; Bovine Amniotic Membrane (BAM), composed of rats treated with lyophilized BAM graft; Decellularized Tilapia Skin (DTS), consisting of animals subjected to grafting with the DTS matrix. The animals were evaluated on postoperative days 1, 3, 7, and 14 to measure the degree of transparency of the ulcer area and the extent of neovascularization by biomicroscopy. On day 14, the animals were euthanized, and the eyes enucleated for histopathological analysis, which included the evaluation of the reepithelialization process, the inflammatory response, collagen deposition, and neovascularization. As for the biomicroscopic parameters, it was found that on day 14, the opacity degree in the ulcer area, the opacity degree in the central corneal region, and the extent of neovascularization in the lesion area measured in the BAM and DTS groups were significantly higher than those in the Control group, with no statistically significant differences observed between the BAM and DTS groups. As for the histopathological analysis, it was found that corneal reepithelialization occurred satisfactorily in all three treatment groups, with repair of the epithelial layers, although with slight disorganization. However, in the analysis of parameters that assess inflammation, it was found that the inflammatory response induced by the grafts with BAM and DTS was significantly higher than that observed in the Control group, being more intense in the DTS group, although no significant difference was found in relation to the BAM group. Similarly, the neovascularization induced by treatments with BAM and, especially, with DTS was significantly higher than that in the Control group. Moreover, in the quantitative analysis of collagen, no statistically significant differences were found between the treatment groups, both for total collagen and type I collagen. Therefore, these findings demonstrate that, in the corneal ulcer model used in this study, the effect of the decellularized tilapia skin matrix on the repair process of the lesion was inferior to non-intervention, i.e., spontaneous healing, due to the induction of an important inflammatory response.